Aprendizagem motora mediada pela ativação do sistema de neurônios-espelho em pessoas pós AVE: elaboração de um programa em terapia ocupacional e o desenvolvimento de um exoesqueleto de mão - Paiva, Gisele (2024)
Introduction - Interventions based on the Mirror Neuron System constitute a valuable new therapeutic strategy for functional recovery after stroke. Objective - Develop, implement and evaluate a program for motor learning in hemiparetic patients, mediated by the activation of the mirror neuron system, for participation in everyday occupations and describe the genesis of a hand exoskeleton testing its viability in hemiparesis. Method – The research is organized through two studies. Study 1 presents the construction of a motor learning program mediated by the activation of the mirror neuron system for participation in occupations and presents the first explorations of the program with two participants using a quasi-experimental research design of type A-B, implemented after approval by the Ethics Committee of UFSCar and CONEP. Study 2 describes the genesis of the hand exoskeleton, highlighting the collaboration of Occupational Therapy with a multidisciplinary team, especially from the field of Computer Science and describes exploratory experiments combining the motor learning program with an exoskeleton in two participants with hemiparesis. Results – Based on the instruments used, people improved both in the program and with the use of the exoskeleton. This result is in line with the assessment made by the participants themselves. Final considerations – The data obtained, although promising, requires further evidence in future studies using both products: the program and the hand exoskeleton.